Konflik Rempang Dalam Bingkai Media (Analisis Framing Media Online batamtimes.co dan batamnews.co) - Nabila, Mutiara Khansa; An’amta, Dimas Asto Aji (Prodi Sosiologi FISIP ULM, 2024)
The agrarian conflict case that occurred in Rempang Island attracted the attention of the mass media in covering the actual reality. This research aims to examine the framing done by Batamtimes.co and Batamnews.co online media on the agrarian conflict in Rempang Island, published in the period of June - December 2023. The type of research used is descriptive qualitative, with Robert N. Entman's framing analysis model which includes 4 elements of analysis, namely define problems, diagnose causes, make moral judgement, and treatment recommendation. This research also uses the perspective of Berger and Luckman's social construction theory. The results showed that Batamtimes.co and Batamnews.co online media framed the agrarian conflict case by leaning towards the role of the government as a policy maker and emphasising the positive impact of investment projects on the regional economy and society. The construction process by both media is shown by supporting the Rempang Eco City project. This can be seen from how both online media show repeated emphasis that focuses on the development of the Rempang Eco City Project compared to the ongoing conflict. Online media in reporting an event, behind it has a certain purpose with various aspects that are highlighted to be understood by readers. Thus, the result of reality that has been processed by the media can be favourable to one party and detrimental to the other. Therefore, it is important for readers to use other sources in accessing information to get a different perspective.